Free Trade Zones in Oman: A Descriptive Analysis - Hossain, Mohammad Zakir (IJRDO - Journal of Applied Management Science, 2015)
The aim of this paper is to present a descriptive analysis about the free trade zones in Oman. Oman has establishedits Free Trade Zones (FTZ) at the beginning of 2000 in order to diversify its non-oil revenues and investments intoits national economy. In fact, the FTZ of a country provides opportunities to the investors a free access to industrialinfrastructure along with the option of 100 per cent return of their revenues. It also creates boosting internationaltrade relations and Foreign Direct Investments (FDI) of the country.